Cyclic Torsion Behavior of Prestressed Concrete Beams - Shakir Mahmouda, Akram; Ameed Alib, Zahraa (Anbar Journal of Engineering Sciences, 2018)
The nonlinear finite element analysis has become an important tool, for the structural design and assessment of prestressed reinforced concrete members. However, design and assessment of torsion are still done with simplified analytical or empirical design methods. This paper pre-sents results from a numerical analysis using the ANSYS finite element program to simulate a prestressed concrete beams subjected to static and cyclic torque. The eight- node brick ele-ments SOLID65 are used for the idealization of concrete while the reinforcements are idealized by using 3D spar element LINK8. The steel plates are idealized by using three dimensional solid elements SOLID45. The results showed that the general behavior of the finite element models represented by torque- twist angle relationships show good agreement with the experimental results from the Abdullah’s beams.